PENGARUH PENERAPAN PENDEKATAN OPEN ENDED TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 136 PEKANBARU - Suryani, Rahmi; Syahrilfuddin, Syahrilfuddin; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low of mathematics learning outcomes of grade V students of SD Negeri 136 Pekanbaru. This is because students only listen and memorize the material that has been given by the teacher, the low creativity of students in solving problems in learning, and the students only focus on the material that has been submitted by the teacher. This study aims to determine the number of learning between students who use the open approach with students who learn conventionally. This type of research is a quasi-experimental research with the subject of a student study of class V SD Negeri 136 Pekanbaru. The results showed that there is an open relationship to the outcomes of learning mathematics students V SD Negeri 136 Pekanbaru. This can be seen from the increase of mathematics learning outcomes from the average of the initial test 35,161 to 71,290 in the final test with an average increase of 0.600 medium category. While the control class average averaged 37,177 initial tests to 47,984 in the final test with an average increase of 0.161 low category. The open ended approach provides a strong relationship with the coefficient of 0.721 and the coefficient of determination 51.99%, in other words the approach of open ended student learning outcomes.Keywords: Open Ended Approach, Learning Outcomes